KINERJA INSPEKTORAT KABUPATEN KAMPAR DALAM PENGAWASAN PENGELOLAAN DANA APBDESA (STUDI KASUS: ANGGARAN DAN PENDAPATAN BELANJA DESA TANJUNG KARANG KABUPATEN KAMPAR PROVINSI RIAU TAHUN 2018-2019) - Clarisa, Cindy; ', Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to evaluate the performance of the Kampar Regency Inspectorate in supervising the management of Village Revenue and Expenditure Budget (APBDesa) funds in Tanjung Karang Village, Kampar Regency, Riau Province, during 2018-2019. The Inspectorate plays a crucial role in ensuring transparency, accountability and efficiency in the management of APBDesa funds, which are important resources for development and public services at the village level. The research method uses a descriptive approach and a qualitative type of research by analyzing various related documents, financial reports, and the results of audits conducted by the Inspectorate. An interview is communication carried out in two directions, either directly or indirectly in the form of questions and answers in order to obtain information from the informant through question points that have been prepared by the author so that the information obtained is in accordance with the problem being researched. According to Kvale and Brinkmann in Creswell (2014: 241), interviews should be more collaborative, where the researcher and participant tend to be balanced in the process of questioning, interpreting and reportin. The findings show several critical aspects in the management of APBDesa funds in Tanjung Karang Village, including indications of irregularities, administrative negligence, and deficiencies in financial reporting. The resulting recommendations include improving the internal monitoring system at the village level, increasing the capacity of village financial managers, and strengthening coordination between the Inspectorate and the village government and district government. Follow-up actions taken include restructuring village financial management procedures, training for village officers, and tighter supervision of financial reporting. Follow-up supervision by the Inspectorate refers to steps taken after carrying out monitoring or audit activities to ensure that findings, recommendations , or problems identified in the supervision report are followed up properly by the party being supervised. The following are several supervisory follow-up steps that are usually carried out by the Inspectorate, such as: submission of findings reports, follow-up meetings, follow-up action plans, monitoring and evaluation, preparation of final reports, disciplinary action, reporting to higher parties. Keywords: Performance Of The Inspectorate, Apbdesa, Tanjung Karang Village, Kampar Regency, Riau Province.